Do executive function and family factors predict children’s preference for trendy over classic toys? An experimental investigation - Gavrilova, Margarita; Sukhikh, Vera; Veresov, Nikolay (Frontiers in Psychology, 2023)
In the last decade, global trends and social media have covered almost the entire world, including children population. The toy industry is filled with new items whose popularity has been triggered by viral publications on social networks or by popular animated films. The present experimental study is the first to (i) describe the characteristics of toy choice in the context of the spread of global trends, and (ii) examine the influence of family and individual child characteristics on the dependence on trends in toy choice. The sample consisted of N = 127 children aged 3-4 years. Сhildren had individual assessment of non-verbal intelligence main executive function skills (cognitive flexibility, working memory and inhibition control) and took part in the experiment, while their parents completed a questionnaire on family background. Analysis of children's answers about the reason for choosing a particular toy indicates uncertain motivation in choosing a trendy toy in contrast to the classic ones. It is reflected in the fact that children do not know what exactly and how they will play with it. It is revealed that boys are 1.66 times more likely to prefer the trendy toy than girls. It was also found that as inhibitory control increased, children were less dependent on tendencies to choose toys.